2021
DOI: 10.1109/access.2021.3053763
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chronic Kidney Disease - A Machine Learning Perspective

Abstract: Chronic Kidney Disease is one of the most critical illness nowadays and proper diagnosis is required as soon as possible. Machine learning technique has become reliable for medical treatment. With the help of a machine learning classifier algorithms, the doctor can detect the disease on time. For this perspective, Chronic Kidney Disease prediction has been discussed in this paper. Chronic Kidney Disease dataset has been taken from the UCI repository. Seven classifier algorithms have been applied in this resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(75 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…Many studies have been carried out in order to explore mechanisms for handling missing values in different fields [5][6][7][8][9][10][11][12][13]. Although choosing the method may be difficult, most studies conclude that imputation is better than removing data due to the fact that deleting data could bias datasets as well as subsequent analyzes on these [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out in order to explore mechanisms for handling missing values in different fields [5][6][7][8][9][10][11][12][13]. Although choosing the method may be difficult, most studies conclude that imputation is better than removing data due to the fact that deleting data could bias datasets as well as subsequent analyzes on these [14].…”
Section: Introductionmentioning
confidence: 99%
“…The feature weight will be high only when the feature is able to differentiate it among the instances of different classes and attain a similar weight for the same class instances. It was noted that the feature set selected by LASSO provided better performance when compared to the other two feature selection algorithms [23]. Hence in this work, features selected by LASSO are considered for further experimental analysis.…”
Section: Feature Selectionmentioning
confidence: 99%
“…The feature extraction by multi labeled has grabbed attention and also shown significant progress in the selection of features. The least absolute shrinkage and selection operator (LASSO) [23] is a common high-dimensional data analysis technique that can perform feature selection and regularization simultaneously. LASSO can accomplish the selection of variables and regularization that can enhance the interpretation process and accuracy of prediction.…”
Section: B Feature Selection and Classification Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polat et al [7] showed an application of a Support Vector Machine variant for patient classification to the same dataset. Chittora and colleagues [22] applied numerous machine learning classifiers and their variants for patient classification. Few studies published recently employed datasets different from the UC Irvine ML Repository one.…”
Section: Introductionmentioning
confidence: 99%